A chemical genetic screen reveals that iminosugar inhibitors of plant glucosylceramide synthase inhibit root growth in Arabidopsis and cereals. Issue 1 (December 2018) - Rugen, Michael; Vernet, Mathieu; Hantouti, Laila; Soenens, Amalia; Andriotis, Vasilios; Rejzek, Martin; Brett, Paul; van den Berg, Richard; Aerts, Johannes; Overkleeft, Hermen; Field, Robert
Abstract Iminosugars are carbohydrate mimics that are useful as molecular probes to dissect metabolism in plants. To analyse the effects of iminosugar derivatives on germination and seedling growth, we screened a library of 390N -substituted iminosugar analogues against Arabidopsis and the small cereal Eragrostis tef (Tef). The most potent compound identified in both systems, N -5-(adamantane-1-yl-ethoxy)pentyl-l -ido -deoxynojirimycin (l -ido -AEP-DNJ), inhibited root growth in agar plate assays by 92% and 96% in Arabidopsis and Tef respectively, at 10 µM concentration. Phenocopying the effect ofl -ido -AEP-DNJ with the commercial inhibitor (PDMP) implicated glucosylceramide synthase as the target responsible for root growth inhibition.l -ido -AEP-DNJ was twenty-fold more potent than PDMP. Liquid chromatography-mass spectrometry (LC-MS) analysis of ceramide:glucosylceramide ratios in inhibitor-treated Arabidopsis seedlings showed a decrease in the relative quantity of the latter, confirming that glucosylceramide synthesis is perturbed in inhibitor-treated plants. Bioinformatic analysis of glucosylceramide synthase indicates gene conservation across higher plants. Previous T-DNA insertional inactivation of glucosylceramide synthase in Arabidopsis caused seedling lethality, indicating a role in growth and development. The compounds identified herein represent chemical alternatives that can overcome issues caused by genetic intervention. These inhibitors offer the potential to dissect the roles of glucosylceramides in polyploid crop species.